Learning Facilities and Pupils’ Academic Performance in Public Primary Schools in Ondo North Senatorial District, Nigeria - Deborah Olukemi Anjorin (Eduvis : Jurnal Manajemen Pendidikan Islam, 2026)
Concerns about declining academic performance in public primary schools in Nigeria have increasingly been linked to inadequate provision and poor maintenance of learning facilities. These facilities are essential for creating a conducive learning environment and supporting effective teaching and learning processes. This study examined the relationship between learning facilities and pupils’ academic performance in public primary schools in Ondo North Senatorial District, Nigeria, with a specific focus on the availability and maintenance of such facilities. The study adopted a descriptive survey research design complemented with an ex post facto approach. A multi-stage sampling technique was used to select 130 teachers from 39 public primary schools. Data were collected using a researcher-developed Learning Facilities Questionnaire (LFQ) and a Pupils’ Academic Performance Proforma (PAPP). The reliability coefficient of the LFQ was established at 0.79. Data were analysed using descriptive statistics and Pearson Product-Moment Correlation at a 0.05 level of significance. The findings revealed that the availability and maintenance of learning facilities in the study area are generally low. However, pupils’ academic performance was found to be high. The results further indicated significant positive relationships between the availability of learning facilities and pupils’ academic performance, as well as between the maintenance of facilities and academic performance. The study concludes that although learning facilities are inadequate, their availability and condition remain important factors associated with pupils’ academic outcomes. The study contributes to knowledge by providing context-specific evidence and by examining both availability and maintenance of facilities within a unified analytical framework.